2005
DOI: 10.1126/science.1115079
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Translational Initiation by Let-7 MicroRNA in Human Cells

Abstract: MicroRNAs (miRNAs) are approximately 21-nucleotide-long RNA molecules regulating gene expression in multicellular eukaryotes. In metazoa, miRNAs act by imperfectly base-pairing with the 3' untranslated region of target messenger RNAs (mRNAs) and repressing protein accumulation by an unknown mechanism. We demonstrate that endogenous let-7 microribonucleoproteins (miRNPs) or the tethering of Argonaute (Ago) proteins to reporter mRNAs in human cells inhibit translation initiation. M(7)G-cap-independent translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

67
1,166
8
21

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,263 publications
(1,262 citation statements)
references
References 24 publications
67
1,166
8
21
Order By: Relevance
“…Plant miRNAs are also methylated on the ribose of the last nucleotide, a modification presumably involved in protecting miRNAs from 3′ end uridylation and degradation, whereas animal miRNAs do not appear to be modified Yu et al 2005). Mechanistically, most animal miRNAs are only partly complementary to their targets and mediate silencing primarily by translational repression, although localization to the processing bodies may also affect RNA stability (Humphreys et al 2005;Liu et al 2005b;Pillai et al 2005;Wienholds and Plasterk 2005;Zamore and Haley 2005). In contrast, most plant miRNAs have near-perfect complementarity to their targets and trigger predominantly mRNA cleavage (Carrington and Ambros 2003;Schwab et al 2005).…”
Section: Additional (Derived?) Functions Of the Rnai Machinerymentioning
confidence: 99%
“…Plant miRNAs are also methylated on the ribose of the last nucleotide, a modification presumably involved in protecting miRNAs from 3′ end uridylation and degradation, whereas animal miRNAs do not appear to be modified Yu et al 2005). Mechanistically, most animal miRNAs are only partly complementary to their targets and mediate silencing primarily by translational repression, although localization to the processing bodies may also affect RNA stability (Humphreys et al 2005;Liu et al 2005b;Pillai et al 2005;Wienholds and Plasterk 2005;Zamore and Haley 2005). In contrast, most plant miRNAs have near-perfect complementarity to their targets and trigger predominantly mRNA cleavage (Carrington and Ambros 2003;Schwab et al 2005).…”
Section: Additional (Derived?) Functions Of the Rnai Machinerymentioning
confidence: 99%
“…However, miRNAs also interfere with translation at the initiation step. Analysing of the effects of both exogenously provided miRNA-like siRNAs or endogenous miRNAs on the translation of their reporter and endogenous targets in human cells showed that the 5 0 cap is required for miRNA-mediated translational repression, because IRES initiated translation or tethering eIF4E and eIF4G to the reporter was immune to miRNAs (Humphreys et al, 2005;Pillai et al, 2005). The two reports disagree with the prerequisite of the poly(A) tail for the inhibition, but in cell free translation system both the 5 0 cap and the poly(A) tail has been shown to be required for recapitulating miRNAmediated translational repression .…”
Section: Mechanism(s) Of Mirna-mediated Gene Regulationmentioning
confidence: 99%
“…2); it still remains to be deciphered which of these model mechanisms are cause and consequence of translational repression. miRNAs affecting initiation steps only affect capdependent translation, possibly through m 7 G cap recognition (Refs 46,47,48,49,50). Argonaute proteins contain structural similarities to the cap-binding protein eIF4E, and thus it has been suggested that translational repression may occur due to competition between argonaute and eIF4E for binding to the cap structure (Ref.…”
Section: Mechanism(s) Of Mirna Actionmentioning
confidence: 99%